Sequencing of mitochondrial genomes using the Precision ID mtDNA Whole Genome Panel. Issue 21 (6th August 2018) - Pereira, Vania; Longobardi, Antonio; Børsting, Claus
Abstract: Massively parallel sequencing offers a fast and cost‐effective method for sequencing of the whole mtDNA genome. The Precision ID mtDNA Whole Genome Panel amplifies the entire mtDNA genome in two multiplex PCRs with 81 primer sets using the Ion AmpliSeq™ technology. In this study, the performance of the panel was evaluated by testing different amplification methods (two‐in‐one or conservative), the number of PCR cycles (21, 23, and 25), and different reaction volumes (recommended volume or half‐volume). Furthermore, a dilution series, controlled mtDNA mixtures, and casework samples were also sequenced. The normalised read depths of the individual fragments were highly consistent irrespectively of the amplification methods or reaction volumes used. The sequencing output matched the mixture ratios of the controlled mtDNA mixtures indicating that the sequencing results were a loyal representation of the input DNA. Complete mtDNA profiles were generated from <10 pg genomic DNA. Seven fragments with relatively low read depths and large variations in read depth were identified. One of these fragments covered part of the control region and the hypervariable region II.